# How do you factor c square minus 5c plus 6?

In Uncategorized

# Factor 25a squared minus 20ab plus 4b squared?

This is not a difficult factorisation, as it is merely a normal factorisation with "a" stuck on the end of each number..
25a(2) - 20ab + 4b(2).
(2b-5a)(2b-5a).
This is:.
2bx2b=4b(2).
2bx-5a=-10ab (twice).
-5ax-5a=25a

# Factor x cubed plus x squared minus 3x minus 3?

xÂ³ + xÂ² - 3x - 3 = (x + 1)(x + â3) (x - â3).

# How do you factor x squared plus x minus 1?

Normally when you factor a polynomial, it is to make a problem easier. This is a polynomial of the form ax 2 + bx - c, where a=b=c=1. Since a=1, to factor this polynomial nicely we would have to find two factors of c=1 that add up to b=1. Since the factors of 1 are -1 and 1, the possible numbers to… add to are (-1) + (-1) = -2; 1 + (-1) = 0; and 1 + 1 = 2. None of these can add up to 1 (our b), so a nice answer is impossible. However, when you factor, you are actually just finding solutions. For example, x 2 -3x+2= (x-1)(x-2). If x 2 -3x+2=0, then either x-1=0 or x-2=0, so x=1 or x=2. Anything to the half power, is the square-root, so we write, using the quadratic formulas (b +/- (b 2 - 4ac) 1/2 )/(2a), the solutions of x 2 + x + 1 are (1 +/- (-3) 1/2 )/2. Since i represents (-1) 1/2 , we can factor x 2 +x+1 = [x - 1/2 + i (3 1/2 )/2] [x - 1/2 - i (3 1/2 )/2] . ( Full Answer )

# Factor x squared plus x minus 10?

to factor this equation you need to use the quadratic formula: in this question a=1, b=1, c= -10 so after you plug in those number you answer would be: x= (-1+ or - the square root of -39) divided by 2

# How do you factor 2x squared minus 13x plus 15?

This is a quadratic equation, and so you it falls under the rule: ax squared + bx + c. This means you need to times the 2x squared by 15, which is 30. Then you need to find the factors of thirty, i.e. 3 and 10, 15 and 2, 5 and 6. You need to find the pair of factors that add to make -13x, which woul…d be -3 and -10. you then need to put these into the equation - it would become 2x squared -10x (as one equation) and -3x +15 would be another equation. we can see that 2x squared and -10x have 2x in common, and so the answer for that would be 2x (x - 5). the second equation would be -3 (x - 5). the two equations have x - 5 in common, and that would make up the first set of brackets. you then add the rest (2x - 3) and your answer would be (x - 5) (2x - 3). ( Full Answer )

# How do you factor 2x cubed minus 5x squared plus 5x minus two?

2x 3 - 5x 2 + 5x - 2 = x(2x 2 -5x+3) + 2x - 2 = x(2x-3)(x-1) + 2(x-1) = (x-1)[x(2x-3)+2] = (x-1)(2x 2 -3x+2) I did it by trial and error, through experience -- no set procedure. (2x 2 -3x+2) cannot be factored, which is evidenced by calculating (b 2 -4ac), where a = 2; b=-3; and c=2 fro…m the expression (2x 2 -3x+2). (b 2 -4ac) = (9-16) = -7, which has no real square root value. That is, sqrt(-7) is an imaginary number. ==== ( Full Answer )

# How do you factor C squared plus C minus 56?

c^2 + c - 56 = (c - 7)(c + 8) using the factoring rule: c -7 -7c x x + c 8 8c c^2 -56 c

# How do you factor 2x squared minus 5x plus 2?

Using the quadratic formula-- ((negative b plus or minus the square root of b squared minus 4ac) divided by (2a)) you'll want to google that so you can see it in numerical form. a, b, and c are the coefficiants of your three terms ( 2 is a, -5 is b, and 2 is c) The answer is (x-2)(2x-1).

# How do you factor w squared minus 13w plus 48?

w 2 - 13w + 48 You want to write the equation in the form (w+a)(w+b). However, if this particular equation could be written in this form, there would be at least one value of x where y = 0. There are no such solutions for this equation, so it cannot be factored into this form. However, you can fa…ctor it if you separate 48 into 42.25 + 5.75: w 2 - 13w + 48 = (w - 6.5) 2 + 5.75 = (w - 6.5)(w - 6.5) + 5.75 ( Full Answer )

# X squared plus 3x minus 6?

X 2 +3x-6=0 A=1 B=3 C=-6 D=B 2 -4AC=3 2 -4*1*-6=33 X1= (-B+âD)/(2A)=(-3+â33)/(2*6)=1,372281323 X2= (-B-âD)/(2A)=(-3-â33)/(2*6)=-4,372281323

# How do you factor z squared plus 7z plus 6?

The procedure for factoring z 2 +7z+6 is as follows: First, we must look at the number in front of the first variable. In this case, it is a 1. Then we look at the last number in the expression, which is a 6 (the expression must be arranged in descending order by the exponents of the variab…les). Now, we multiply these two numbers together. 1 x 6 = 6 We need to factors of 6 that when added together equal 7. The factors of 6 are as follows 1 x 6 2 x 3 The first set of factors is the only set that adds up to equal 7. So now we break apart the middle term into 1 and 6, so that it looks like this: z 2 +z+6z+6 Now we group the expression like this (z 2 +z)+(6z+6) With the parenthesis like this, we can begin pulling out common factors, leaving the expression looking like this z(z+1)+6(z+1) Because the contents of the sets of parenthesis are the same, we can combine the z and the 6 to get the fully-factored expression (z+6)(z+1) ( Full Answer )

# What are the factors of q cubed minus q squared plus 2q minus 2?

q 3 - q 2 + 2q - 2 = (q 2 + 2)(q - 1). * If you are prepared to enter the realm of complex numbers (where i = â(-1) ), then (iâ2) 2 = 2(i 2 ) = -2, and q 2 + 2 = q 2 - (iâ2) 2 = (q - iâ2)(q + iâ2); and, in this case, the complete factorizat…ion is q 3 - q 2 + 2q - 2 = (q 2 + 2)(q - 1) = (q - iâ2)(q + iâ2) (q - 1). ( Full Answer )

# Factor X squared plus 2x minus 8?

1) Find two numbers that multiply to -8 and add to 2. Factor of (-8) Sum of (2). This is 2 * (-4)= -8 and -2 + 4= 2. 2) Then put it in factor mode. (X-2)(X+4). Use distributive property. 3) After that, set it to 0. 0= X-2 Add (+) 2 to both sides. Cross out the negative and positive 2's. 0 + 2 is 2 …= X. 4) Do the same for 4. 5) GGOD LUCK & HOPE U PASS :) ( Full Answer )

# What is the factor to 9x squared plus 12x minus 1?

That doesn't factor neatly. Applying the quadratic equation, we find two real solutions: (-2 plus or minus the square root of 5) divided by 3 x = 0.07868932583326327 x = -1.4120226591665965

# What are the factors of 6x squared plus 7x minus 5?

We are looking for a factorization like 6xÂ² + 7x - 5 = (_x + _)(_x - _) where we need to fill in the numbers in the blanks. Since the first and third blanks multiply to 6, they have to be 1 and 6 or 2 and 3. Similarly, the second and fourth blanks multiply to 5 so they must be 1 and 5. By t…rial and error, we arrive at the factorization 6xÂ² + 7x - 5 = (2x - 1)(3x + 5). ( Full Answer )

# How do you factor 12t squared minus t plus 4?

That doesn't factor neatly. Applying the quadratic formula, we findtwo imaginary solutions: (1 plus or minus the square root of -191)divided by 24 t = 0.0416666 repeating + 0.5758447900452189 i t = 0.0416666 repeating - 0.5758447900452189 i where i is the square root of negative one.

# How do you factor 2y squared plus 12y minus 32?

Pull out the common factor of 2 ... 2(y^2+6y-16) Then just factor (y^2+6y-16) ... (y-2)(y+8)

# What is 6x squared plus 5x minus 6 factored out to?

6x 2 + 5x - 6 is factored out to (2x + 3)(3x - 2).

# How do you factor 9x squared plus 27x minus 36?

9x 2 + 27x - 36 = 9(x 2 + 3x - 4) = 9(x + 4)(x - 1)

# How do you factor 3x squared minus 16x plus 5?

3x 2 - 16x + 5 = 3x 2 - x - 15x + 5 = x(3x - 1) - 5(3x -1) = (3x - 1)(x - 5) or I would use the quadratic equation. 3X^2 - 16X + 5 = 0 X = -b +/- sqrt(b^2-4ac)/2a a = 3 b = -16 c = 5 X = -(-16) +/- sqrt[(-16)^2 - 4(3)(5)]/2(3) X = 16 +/- sqrt(256 - 60)/6 X = 16 +/-…sqrt(196)/6 X = (16 +/- 14)/6 X = 5 X = 1/3 check the easy one 3(5)^2 - 16(5) + 5 = 0 75 - 80 + 5 = 0 0 = 0 easy one checks; you try the 1/3 check ( Full Answer )

# Who can factor this x squared plus 2x minus 3?

(x - 1)(x + 3) Think of 2 numbers which added together give +2 and which multiplied together give -3

# How do you factor 2u squared plus 13u plus 6?

I don't factor these. I am lazy, so I use the quadratic formula. -b +/- sqrt(b^2-4ac)/2a a = 2 b = 13 c = 6 u = - 13 +/- sqrt[13^2 - 4(2)(6)]/2(2) u = - 13 +/- sqrt(121)/4 u = [- 13 +/- 11]/4 u = - 1/2 u = - 6 My TI-84 confirms this answer. You check in original equation.… ( Full Answer )

# How do you factor c squared minus 7c plus 10?

To factor this equation... if you have learned before, find 2 numbers that add up to the middle value (-7) and multiply together to have a product of the last value (+10). You can use guess and check for this problem... but if you haven't already found it... the sum of -5 and -2 is -7... and the pr…oduct of -5 and -2 is +10, so we can use the values -5 and -2.... The solution is (c-5)(c-2) = c^2 - 7c + 10. ( Full Answer )

# A minus b plus c whole square?

If you mean (a-b+c)^2, then... .
a^2 - ab + ac - ab + b^2 - bc + ac - bc + c^2 .
= a^2 + b^2 + c^2 - 2ab + 2ac - 2bc.

# What are the factors of 3x squared minus 7x plus 4?

The sum of the coefficients is 3 - 7 + 4 = 0 so (x - 1) is a factor. Thus, 3x 2 - 7x + 4 = 3x 2 - 3x - 4x + 4 = 3x(x - 1) - 4(x - 1) = (3x - 4)(x - 1)

# What are the factors of 8x squared plus 6x minus 9?

8x 2 + 6x - 9 = 8x 2 + 12x - 6x - 9 = 4x(2x + 3) - 3(2x + 3) = (2x + 3)(4x - 3)

# How do you factor x squared minus 9x plus 16?

Since there is an x 2 , we can do this step first: (x )(x ) For this question, we need to use the quadratic formula: -bÂ±â(b 2 -4ac) ----------------- 2a Let me explain some of the symbols and letters first. Â±- is the plus or minus sign. You will perform both separately wh…en we reach this step. â-is the square root sign. The line above 2a is the division line. The letter a represents the quantity of x 2 , which is 1 in this case The letter b represents the quantity of x, which is 9 in this case The letter c represents the quantity of 1, which is 16 in this case Let's plug the numbers in, so your formula will look like this: -9Â±â(9 2 -4(1)(16)) ----------------- 2(1) Simplify: -9Â±â((81)-(64)) ----------------- = 2 -9Â±â(17) ----------------- = 2 -9Â±(4.1231) ----------------- =This is the part where we split off into plus or minus 2 -9+4.1231 ----------------- = 2 -4.8769 ----------------- = 2 -2.4384 (This is one part of your answers. Let's do the minus part now.) -9-4.1231 ----------------- = 2 -13.1231 ----------------- = 2 -6.56155 (This is your second part of your answer. The factorization is below) (x-2.4384)(x-6.56155) ( Full Answer )

# What is x cubed minus 4x squared plus x plus 6 when fully factorized?

x 3 - 4x 2 + x + 6 = (x + 1)(x - 2)(x - 3)

# How do you factor 3x squared minus 3x minus 6?

3x 2 - 3x - 6 = 3(x 2 - x - 2) = 3 (x + 1) (x - 2)

# How do you factor 3x squared minus 15x plus 16?

You will find it too difficult to factor this expression. If you wish to solve for the roots of this quadratic you first need to know what the expression is equal to (so you can write it in the form of ax 2 + bx + c = 0) and then you should use the quadratic formula instead. x = (-b + or - …(b 2 - 4ac) 1/2 ) / 2a ==== The factors are close to (x - 3.45743) and (x - 1.54257), and those are rounded, so you can see why it would be difficult to try and factor the expression. ( Full Answer )

# How do you factor 49x squared minus 84x plus 36?

49x 2 - 84x + 36 = (7x - 6)(7x - 6) or (7x - 6) 2

# What is 9x squared minus 6xy plus y squared minus 81 factored as?

9x 2 - 6xy + y 2 - 81 = (3x - y) 2 - 9 2 = (3x - y - 9)(3x - y + 9)

# How do you factor a plus b quantity squared minus 100?

(a + b) 2 - 100 = (a + b + 10)(a + b - 10).

# How do you factor 2x squared minus 77x plus 119?

2x^2-77x+119 It is not factorable if you are looking for integral factors (whole numbers). You might be able to use the quadratic formula if you wish to solve for the zeros (x-intercepts) of it.

# How do you factor x squared minus 2x plus 2?

That doesn't factor neatly. Applying the quadratic formula, we findtwo imaginary solutions: 1 plus or minus i where i isthe square root of negative one.

# What are the factors of 3X squared minus 14X plus 8?

(x - 4)(3x - 2) 3X 2 - 14X + 8 = 0 X = - b (+/-) sqrt(b 2 - 4ac)/2a a = 3 b = - 14 c = 8 X = - (- 14) (+/-) sqrt[(- 14) 2 - 4(3)(8)]/2(3) X = 14 (+/-) sqrt(196 - 96)/6 X = 14 (+/-) sqrt(100)/6 X = [14 (+/-) 10]/6 X = 4 ---------- X = 2/3 -----------------check …one at least 3(4) 2 - 14(4) + 8 = 0 48 - 56 + 8 = 0 0 = 0 ( Full Answer )

# How do you factor x squared minus x plus 2?

This equation (where the above expression equals 0) has imaginary roots and so will need to be solved using the quadratic formula and the use of the imaginary number i .

# What is 6a squared minus 8ab plus 2a factored as?

6a 2 - 8ab + 2a as you can see a is common to all terms. And 2 is a factor of 6,8, and 2. So 2a is a factor of all three terms: 2a(3a-4b+1)

# What is a squared plus 5a plus 6 divided by a minus 2?

(a 2 + 5a + 6)/(a - 2) = (a + 2)*(a 3)/(a - 2) which cannot be simplified further. It can, however be written as (a 2 - 2a + 7a - 14 + 20)/(a - 2) which is (a + 7) + 20/(a - 2)

# What is 8M minus 4M minus 6 minus 3 plus 5M equals 8 squared minus 1?

8M - 4M - 6 - 3 + 5M = 8 2 - 1 9M - 9 = 64 - 1 9M - 9 = 63 9M - 9 +9 = 63 + 9 9M = 72 9M/9 = 72/9 M = 8

# How do you factor x squared plus 16x minus 348?

x 2 + 16x - 348 cannot be factored. Solving for x with the quadratic formula results in x = -8 - 2â103 and x = -8 + 2â103

# What is the factor of 3x squared plus 15x plus 6?

3x 2 + 15x + 6 = 3*(x 2 + 5x + 2). There are no further rational factors.

# How do you factor x squared plus 16x minus 416?

That doesn't factor neatly. Applying the quadratic formula, we findtwo real solutions: -8 plus or minus 4 times the square root of 30. x = 13.908902300206645 x = -29.908902300206645

# How do you factor x squared plus 9x minus 22?

x 2 + 9x - 22 = x 2 + (11 - 2)x + (11 x -2) = x 2 + 11x -2x + (11 x -2) .
= (x + 11)(x - 2) .

# How do you factor 2y squared plus 9y minus 2?

2y 2 + 9y - 2 this will not factor using integers what is what most algebra teachers will tell you is 'prime' but ... make an equation ... 2y 2 + 9y - 2 = 0 use the quadratic formula to solve y = [-9 (+/-) sq rt (81 -4x2(-2))] / (2x2) y = [-9 (+/-) sq rt (97)] / (4) now separate these y = …[-9 + sq rt (97)] / (4) y = [-9 - sq rt (97)] / (4) rewrite as equal to zero (y - [-9 + sq rt (97)] / (4)) =0 (y - [-9 - sq rt (97)] / (4)) = 0 apply zero product property in reverse (y - [-9 + sq rt (97)] / (4))(y - [-9 - sq rt (97)] / (4)) = 0 these, as weird as they may look, are the factors. ( Full Answer )

# What are the factors of 3x squared minus x plus 4?

That doesn't factor neatly. Applying the quadratic equation, we find two imaginary solutions: (1 plus or minus the square root of -47) divided by 6. x = 0.16666 + 1.142609100066840 i = 1 st root = r 1 x = 0.16666 - 1.142609100066840 i = 2 nd root = r 2 where i is the square root of neg…ative one. Then factor as (x - r 1 )(x - r 2 ) Or you can complete the square to transform the trinomial into the difference of the squares 3x 2 - x + 4 factor out 3 = 3(x 2 -(1/3)x + 4/3) add and subtract (1/6) 2 = 3[x 2 -(1/3)x + (1/6) 2 - 1/36 + 4/3] simplify = 3[(x - 1/6) 2 + 47/36] write 47/36 = - (-47/36) = - (â-1â47/6) 2 = - (iâ47/6) 2 = 3[(x - 1/6) 2 - (iâ47/6) 2 ] write the difference of the squares = 3[(x - 1/6) - (iâ47/6)][(x - 1/6) + (iâ47/6)] = 3[(x - (1 + iâ47)/6)][(x - (1 - iâ47)/6]. ( Full Answer )

# What are the factors of 6x squared plus 7x plus 6?

That doesn't factor neatly. Applying the quadratic formula, we findtwo imaginary solutions: (-7 plus or minus the square root of -95)divided by 12. x = -0.583333 repeating + 0.8122328620674136 i x = -0.583333 repeating - 0.8122328620674136 i where i is the square root of negative one.

# How do you factor x squared plus x minus one?

That doesn't factor neatly. Applying the quadratic formula, we findtwo real solutions: (-1 plus or minus the square root of 5) dividedby 2. x = 0.618033988748949 x = -1.618033988749849

# What is a factor of 5x squared plus 13x minus 6 with work shown?

-6 = 3 x -2 13 = 5 x 3 - 2 â 5xÂ² + 13x - 6 = (5x - 2)(x + 3)

# How do you factor x squared minus 8x plus 12?

Find out what two numbers add up to -8 yet when mutiplied they produce 12 and so: x squared-8x+12 = (x-2)(x-6) when factored